META-SYNTHESIS OF STUDIES ON CORE LEARNING INTEGRATED WITH ETHNOMATHEMATICS FOR ENHANCING MATHEMATICAL CONNECTION ABILITY - Vena Ulya Maulida; Arief Agoestanto; Mulyono Mulyono (Universitas Sembilanbelas November Kolaka, 2026)
This study aims to analyze the CORE learning model integrated ethnomathematics to enhance mathematical connection ability. The research method employed is a Systematic Literature Review using meta-synthesis with a meta-aggregation approach. The reporting of the literature identification and selection process follows the PRISMA 2020 guidelines. Literature was searched in the Google Scholar database using Publish or Perish from 2017 to 2026. The search strategy uses the following combination of Boolean operators: (“CORE learning model” OR “Connecting Organizing Reflecting Extending”) AND (“etnomatematika” OR “ethnomathematics”) AND (“mathematical connection ability” OR “kemampuan koneksi matematis”). The synthesis results indicate that the CORE learning model intergrated with ethnomathematics has the potential to enhance mathematical connection ability through three mechanism: (1) cognitive reinforcement through the systematic implementation of the CORE learning model’s syntax, (2) the application of formal mathematical concepts to contextual situations through local culture, (3) the use of learning media that intergrates the CORE learning model and ethnomathematics, which has been proven to be valid and practical. Thus, the syntax in the CORE learning model can build students’ thinking processes, particularly mathematical connection ability, by integrating ethnomathematics as a context for mathematics learning, thereby making learning more culturally relevant and meaningful.